(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2022)
Community Learning and Development (CLD) practitioners in Scotland have been responsible for supporting people to use Information Communications Technology (ICT) since the 90s. The ubiquitous nature of ICT means that the people and communities we work with, and ourselves, need to understand how we engage with this. However, there is a complex policy landscape and limited research around ICT in CLD and this is affecting how we can use this effectively. Since the term CLD includes different professions, it can be described as pluralistic and there are different philosophies that inform practice. This would indicate that there are shared epistemologies which can form a broad body of practice research, but this is not yet fully realised. This research explores models which can be used to identify shared epistemologies and start discussion about how we practise, specifically around using ICT. The research used mixed methods under a constructivist/interpretivist paradigm to understand how CLD practitioners at Dundee Carers Centre engage with ICT. The findings from this research are not intended to give definitive findings, but to support CLD practitioners to reflect on practice and generate discussion around using ICT. Whilst this research was completed in 2014, it can be used to inform and develop practice during the COVID-19 pandemic.